Comparison of antibacterial properties of two fluoride-releasing and a nonfluoride-releasing pit and fissure sealants - Menon Preetha V; Shashikiran N; Reddy V.V.S (Wolters Kluwer Medknow Publications, 2007)
Occlusal pits and fissures are the most susceptible sites for the development of dental caries and prevention is difficult in the areas of occurrence. Although only 12.5% of all the tooth surfaces are occlusal, these surfaces develop more than two-thirds of total caries experienced by children. The fate of the bacteria is of significance when they are inadvertently sealed by a dental sealant. This study aimed in examining the antibacterial properties of three commercially available sealants, viz., Teethmate-F, Helioseal-F and Helioseal. Antibacterial testing was done by disc diffusion method. Selective agars were used to grow Streptococcus mutans and Lactobacillus acidophilus, which are implicated in the pathogenesis of dental caries. Statistical analysis was carried out using student′s t test. The study proved that Helioseal-F and Helioseal did not possess antibacterial properties and Teethmate-F was the only sealant that showed antibacterial properties.